Effect of the organic and mineral fertilizer on the performance of sugarcane yield in Nariño, Colombia - Volverás-Mambuscay, Belisario (2020)
Introduction. Colombia is the second producer of panela or non-centrifugal sugar (NCS) in the world, after India. In 2016, the department of Nariño had an area in sugarcane (Saccharum officinarum L.) for harvested sugarcane or NCS of 10 533 ha and an average yield of 7.67 t ha-1 for 6.35 % of total production of panela or NCS in the country. Objective. To evaluate the use of organic and mineral fertilizer on the sugarcane yield for panela or NCS production in its first production cycle. Materials and methods. The study was carried out between the months of November 2008 to March 2010 in the village of Villa Ines, Consaca, Nariño; a randomized complete block design was used, considering continuous sowing systems (SEC) and spacing (SE) ajusted NPK levels according to soil analysis, with chemical (FQ) and organic (FO) sources. The yield was evaluated in cane and panela or NCS, and reducing sugars and phosphates. Results. The treatments (T3) SEC-FQ with 168.20 TCH, (T1) SEC-FA with 167.07 TCH and (T5) SE-AO with 167 TCH showed the highest cane yield compared to the other treatments, and where significantly different from the control treatment (T9). In panela or NCS, the best treatment was (T6) SE-FQ (12.1 % conversion and 18.78 t ha-1). The highest value of reducing sugars was (T8) SE-FA with 13.2 % while in phosphates it was (T9) SEC and SE-SF (753 ppm), and SEC-AO (706 ppm). With 1,500 kg ha-1 of commercial organic fertilizer, cane yields above 100 t ha-1 and panela yields or NCSof 15 and 17 t ha-1 in SEC and SE, respectively, were obtained, similar to those achieved with chemical fertilization. In chemical fertilization, with the mixture of sources the use of nitrogen was reduced by 42 % and phosphorus by 18 %, with cane yields 44 % higher than the regional average and panela yields 20 % higher than the control. Conclusion. It was possible to reduce and supply some nutrients of chemically synthesized nutrients without affecting the sugarcane and panela or NCS yields.